Effects of irrigation management on chemical composition of soybeans in the San Joaquin Valley - R Miller; B Beard (California Agriculture, 1967)
The recent cutbacks in acreage allotments in the San Joaquin Valley have caused cotton ranchers with interests in oil-processing facilities to recognize the need for a supplemental oil crop, such as soybeans, to allow continued use of the facilities at or near capacity. Projected population increases in many parts of the world also indicate that a protein crop such as soybean could have increasing importance in meeting future food needs.